1973
DOI: 10.1113/jphysiol.1973.sp010102
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous convergence on to the climbing fibre input to cerebellar Purkyně cells

Abstract: SUMMARY1. In cats anaesthetized with Nembutal, the cutaneous receptive fields of individual cerebellar climbing fibres were assessed by recording the climbing fibre responses of single Purkyn6 cells following controlled mechanical stimulation (air jets, vibration, taps, pressure) of the foot pads of all four limbs and of the hairy skin of the limbs and the body.2. Three major types of cutaneous receptive fields of individual climbing fibres were recognized: (a) restricted fields generally confined to the dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

1975
1975
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 17 publications
4
8
0
Order By: Relevance
“…First, within the rostral dorsal accessory olive (the site of relay for climbing fiber paths terminating in the medial C1 zone), descending and ascending projections overlap heavily (Berkley and Worden, 1978;Bull et al, 1990). We found that complex spikes of single Purkinje cells could be evoked by both SR and CP stimulation, providing unequivocal evidence that descending and ascending paths can converge on the same olivary neurons supplying climbing fibers to the relevant region of cortex, as reported previously (Provini et al, 1968;Miller et al, 1969;Leicht et al, 1973;Allen et al, 1974).…”
Section: Methodological Considerationssupporting
confidence: 84%
See 1 more Smart Citation
“…First, within the rostral dorsal accessory olive (the site of relay for climbing fiber paths terminating in the medial C1 zone), descending and ascending projections overlap heavily (Berkley and Worden, 1978;Bull et al, 1990). We found that complex spikes of single Purkinje cells could be evoked by both SR and CP stimulation, providing unequivocal evidence that descending and ascending paths can converge on the same olivary neurons supplying climbing fibers to the relevant region of cortex, as reported previously (Provini et al, 1968;Miller et al, 1969;Leicht et al, 1973;Allen et al, 1974).…”
Section: Methodological Considerationssupporting
confidence: 84%
“…Regardless of their origin, the COCP and SOCP climbing fiber responses share a common final pathway from the olive to the cerebellar cortex (Provini et al, 1968;Miller et al, 1969;Leicht et al, 1973;Rowe, 1977;Andersson and Nyquist, 1983). The pattern of innervation of olivary neurons by inhibitory and excitatory afferents is random, with no obvious preference for one type of terminal targeting intraglomerular or extraglomerular dendrites .…”
Section: Possible Sites Of Modulationmentioning
confidence: 99%
“…Clearly, in the light of the present findings and those of the aforementioned studies (Eccles et al 1972;Leicht et al 1973a), CFs are capable of transmitting very precise information regarding the location and intensity of peripheral sensory events to individual Purkinje cells. The results reported by Oscarsson and his collaborators may be partially attributed to differences in experimental procedure.…”
Section: T S Miles and M Wiesendanger Discussionsupporting
confidence: 69%
“…In the lower third of the face, the mandibular skin opposite the canine tooth was a low threshold area, as were the supraorbital sensory hairs in the upper third of the face. Cells having discontinuous receptive skin fields were found less commonly on the face than has been reported for the limbs (Leicht et al 1973a). This may possibly be attributed to the high density of innervation of the face area, and in any case this is consistent with the distribution of receptive fields that has been described for cells in the trigeminal nuclei (Gordon et al 1961; Darian-Smith, Proctor & Ryan, 1963;Rowe & Sessle, 1972).…”
Section: Ipsilateral VIImentioning
confidence: 74%
See 1 more Smart Citation